(untitled) (Research, Society and Development, 2022)
AMI is the leading cause of death in Brazil and worldwide. It is characterized by the destabilization of the atherosclerotic plaque that will involve the rupture and soon after the formation of a thrombus, which may totally or partially obstruct the coronary artery. The objective of the study is to know and study the performance of the nursing team in front of the patient diagnosed with Acute Myocardial Infarction in an emergency. This is an exploratory and descriptive study. The study was developed with ten nursing professionals from a medium-sized hospital in Vale do Taquari who work in the emergency sector. The results showed that both nurses and nursing technicians follow the same behavior towards patients with AMI and know how to manage them in an adequate and organized way, as each one has a role during the care; the conduct before the relatives of the patients described was to pass on information regarding the patient’s condition and how to proceed during the care. In some cases, care is provided by a professional psychologist. Regarding the patient’s condition, only physicians provide this information and the SAE was reported as a very important tool, promoting better care and organization of the team, reflecting on the patient’s improvement. We conclude that the performance of the nursing team is extremely important for the care of AMI, as well as the behavior of the team reflects in the care of the patient and family.